Phlebotominae (Diptera : Psycodidae) fauna in the Chaco region and cutaneous Leishmaniasis transmission patterns in Argentina - Salomón, Oscar Daniel (2008)
Fil: Salomón, Oscar Daniel. Instituto Nacional de Medicina Tropical; Argentina.